α-Scattered spaces - David A. Rose (International Journal of Mathematics and Mathematical Sciences)
α-scattered spaces, spaces whose α-topology is scattered, are introduced and used to slightly extend a recent result of A. V. Arhangel'skii and P. J. Collins [1]. Strong irresolvability of J. Foran and P. Liebnitz [6], is also characterized in terms ofthe α-topology, and it is shown that a recent theorem of Julian Dontchev [5] in essence maximally extends the Arhangel'skii-Collins result.